2011
DOI: 10.4111/kju.2011.52.4.233
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cystectomy and Orthotopic Bladder Substitution Using Ileum

Abstract: Over the past decade, continent urinary diversion, especially orthotopic bladder substitutions, has become increasingly popular following radical cystectomy for bladder cancer. The ultimate goal of orthotopic bladder substitution is to offer patients the best quality of life, similar to that of patients with native bladders. To achieve that purpose, surgeons should be familiar with the characteristics of good candidates for neobladders, the possible intraoperative and postoperative problems related to the surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…The use of the ileum for orthotopic bladder substitution has gained general acceptance within the past decade, and orthotopic continent diversions have become the "gold standard" reconstructive procedure after radical cystectomy 11. Nowadays, all cystectomy patients are potential candidates for a neobladder 2,3,5. Also, contraindications for orthtopic neobladder are fewer than in the past.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of the ileum for orthotopic bladder substitution has gained general acceptance within the past decade, and orthotopic continent diversions have become the "gold standard" reconstructive procedure after radical cystectomy 11. Nowadays, all cystectomy patients are potential candidates for a neobladder 2,3,5. Also, contraindications for orthtopic neobladder are fewer than in the past.…”
Section: Discussionmentioning
confidence: 99%
“…A radical cystectomy is accepted by many surgeons as a proper treatment for patients with muscle invasive bladder cancer. It is also a suitable option for select patients with high-risk of non-muscle-invasive bladder cancer, and is used as a effective treatment modality for recurrent or refractory tumors after bladder preservation therapies 2. The final decision of urinary diversion in the individual patient is made after many considerations: it should be considered the comorbidities, possibility of complete recovery, technical feasibility, expected functional outcomes, and comply with the patient's choice if possible.…”
Section: Introductionmentioning
confidence: 99%
“…Ileal urinary diversion after RCP is the safest for cancer control, have the lowest complication rates, and afford the easiest adjustment for patients' lifestyle (13).…”
Section: Discussionmentioning
confidence: 99%
“…Hekal et al (12) and Zippe et al (3) reported that in a group of patients who underwent nerve sparing RCP the recovery of erectile function after surgery was better. In a review article, Park and Ahn concluded that orthotopic continent diversion provides good quality of life with few long-term complications (13). For the first time, in the present study we aimed to test whether there are differences between patients with an ileal conduit urinary diversion and those with orthotopic bladder substitution, in terms of EF and SD after RCP.…”
Section: Introductionmentioning
confidence: 93%
“…So far, more than 30 articles have made comparisons of the impact of different types of urinary diversion on patient QoL. [3] A major obstacle is lacking of disease-specific QoL instrument, which universally compares patients after urinary diversion. In addition, the concept of QoL differs significantly between cultures, countries, and races.…”
Section: Introductionmentioning
confidence: 99%